The effect of brand personality on brand equity for SMEs brand - Mat Daud, Suhaini; Abd Ghani, Noor Hasmini; Abdullah, Sahadah (2016)
Current business landscape is characterized by a highly challenging and competitive environment. Thus, it is imperative for companies to increase their competitiveness level in the market. In the strategic brand management literature, little attention has been paid to investigating the impact of brand personality on brand equity. Hence, the purpose of this paper is to discuss empirically the effect of brand personality on brand equity in the Small and Medium Enterprises (SMEs) food industry in Malaysia.The data were collected using intercept survey of 538 consumers of SMEs food product in Northern region of Malaysia.The gathered data was further analysed using Structural Equation Modeling Smart PLS 3.0 software.Results revealed that brand personality does significantly affect brand equity and its dimensions.